Evaluation of HPV infection and presence of licensed HPV vaccine genotypes among genital warts in Foshan, China - Huang, Zeqi; Yao, Shaonuan; Zou, Lin; Xie, Weixian; Xie, Dongde; Li, Weiwei; Tan, Deyou; Shuai, Jiangang (Frontiers in Microbiology, 2024)
This study aimed to evaluate the prevalence of human papillomavirus (HPV) infection and presence of licensed HPV vaccine genotypes among patients with genital warts in Foshan, China from 2015 to 2022, to provide useful references for the detection, prevention and control of genital warts in Foshan. Methods: The present study retrospectively analyzed the HPV detection rates in patients with genital warts. A total of 1,625 patients were seen at the Second People's Hospital of Foshan, Guangdong Province, China, from 2015 to 2022. Samples were collected from various lesions and genotyped for 21 genotypes of HPV by infusion hybridization. The classification principle of HPV genotypes in this study: (1) Based on the relationship between HPV and carcinogenicity；(2) Based on the number of HPV genotypes infected；(3) Based on the HPV genotypes of licensed HPV vaccines.The detection rate of any HPV in patients with genital warts was 80.37% (1306/1625). The detection rates of HPV for low-risk infection, co-infection and high-risk infection were 49.48% (804/1625), 24.92% (405/1625) and 5.97% (97/1625), respectively. Single infection was the predominant type (51.94%, 844/1625). HPV-6 and HPV-11 were the predominant types of single infection; HPV-6 and HPV-52 were the predominant types of paired combinations of multiple infection. 82.22% (1336/1625) of the cases had an age distribution of ≤24, 25-34, and 35-44. The distribution of some HPV genotypes had age specificity, annual specificity and gender specificity. The genotype detection rates of 2v, 4v and 9v showed a decreasing trend with ages (all P<0.05). The genotype detection rates of 4v and 9v showed a decreasing trend over the 8-year period (both P<0.05). The genotype detection rates of 4v and 9v in the male group were higher than those in the female group (both P<0.05). The genotype detection rate of 9v was significantly higher than that of 2v and 4v in the female group (both P<0.05).Our study demonstrated that low-risk infection and single infection were the main types of HPV infection in patients with genital warts, mainly among young patients. Our study provides epidemiological data for the detection, prevention and control of genital warts in China.